2005
DOI: 10.1287/orsc.1050.0153
|View full text |Cite
|
Sign up to set email alerts
|

A Socially Embedded Model of Thriving at Work

Abstract: Thriving describes an individual’s experience of vitality and learning. The primary goal of this paper is to develop a model that illuminates the social embeddedness of employees’ thriving at work. First, we explain why thriving is a useful theoretical construct, define thriving, and compare it to related constructs, including resilience, flourishing, subjective well-being, flow, and self-actualization. Second, we describe how work contexts facilitate agentic work behaviors, which in turn produce resources in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

84
2,212
2
30

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,038 publications
(2,328 citation statements)
references
References 73 publications
84
2,212
2
30
Order By: Relevance
“…By utilizing the componential theory of creativity (Amabile, 1983), Spreitzer, Sutcliffe, Dutton, Sonenshein and Grant's (2005) model of thriving and Quinn and Dutton's (2005) theory of coordination they showed that LMX was positively related to employees' feelings of energy, which in turn were related to a high level of involvement in creative work. in a longitudinal, multisource and multi-level study looked at both LMX and TMX (Team-Member Exchanges).…”
Section: Relational Perspectivesmentioning
confidence: 99%
“…By utilizing the componential theory of creativity (Amabile, 1983), Spreitzer, Sutcliffe, Dutton, Sonenshein and Grant's (2005) model of thriving and Quinn and Dutton's (2005) theory of coordination they showed that LMX was positively related to employees' feelings of energy, which in turn were related to a high level of involvement in creative work. in a longitudinal, multisource and multi-level study looked at both LMX and TMX (Team-Member Exchanges).…”
Section: Relational Perspectivesmentioning
confidence: 99%
“…Contentment, by contrast, is correlated positively with the 'pleasure' dimension and negatively with the 'arousal' dimension. Applied to the job, employees with high Enthusiasm-with high pleasure and stimulation from their work-are said to have feelings central to the model of ''thriving'' (Spreitzer et al 2005), while conversely those with low Enthusiasm express feelings of depression, who take no pleasure from their work and are passive. Those with high Contentment find their jobs acceptable but are said to have a ''resigned satisfaction'', while conversely those with low Contentment express feelings of anxiety, being both aroused by and experiencing displeasure from their work (Grebner et al 2005;Warr 2007: 22).…”
Section: Theory and Prior Evidence Linking Job Characteristics And Jomentioning
confidence: 99%
“…Behavioural energy represents the action-related construct of productive organisational energy and the degree to which groups engage in active, focused, and purposeful behaviours to realize organizational objectives (Spreitzer, Sutcliffe, Dutton, Sonenshein & Grant, 2005;. Individual behavior and social interactions are important drivers of energy creation for sustained business process execution and business performance (Schiuma et al, 2007).…”
Section: Productive Organisational Energymentioning
confidence: 99%